Investigation of Electron Distribution Functions Associated With Whistler Waves at Dipolarization Fronts in the Earth's Magnetotail: MMS Observations. Issue 9 (11th September 2020) - Grigorenko, E. E.; Malykhin, A. Y.; Shklyar, D. R.; Fadanelli, S.; Lavraud, B.; Panov, E. V.; Avanov, L.; Giles, B.; Le Contel, O.
Abstract: Using burst mode Magnetospheric Multiscale (MMS) observations in the plasma sheet (PS), we study the dynamics of electron anisotropy and its relation to quasi‐parallel narrowband whistler bursts in 37 dipolarization fronts (DFs) propagating in the Earth's magnetotail along with fast flows at −25 R E ≤ X ≤ −17 R E . The bursts were observed at the DFs and behind them in the dipolarizing flux bundle (DFB) region with frequencies f peak (0.1–0.6) f ce ( f c e is electron gyrofrequency) and durations approximately a few seconds. The majority of the whistler waves were associated with perpendicular electron temperature anisotropy T PER / T PAR > 1, and the value of this anisotropy decreased by the end of the bursts suggesting electron scattering by the waves. We found that the major contribution to the growth rate of whistler waves is made by resonant electrons with energies W res 1–5 keV and pitch angles α res 40–75° and 100–135°. In the majority of cases, the largest W res was observed at the DF and immediately behind it, while in the DFB the W res decreased. The sources of the majority of whistler bursts were not confined near the neutral plane but could be extended into the PS where the perpendicular anisotropy of the local electron distribution provided the positive growth rate of the whistler waves. We show that the observed whistler waves play a significant role in the dynamics of electron velocity distribution in DFs, leading to energy exchange between various parts of electron population and constraining temperature anisotropy of electron distribution. Key Points: Electron distribution function is highly variable on time scales of short narrowband quasi‐parallel whistler bursts at and behind DFs Electrons with energies 1–5 keV and pitch angles 40–75° and 100–135° make the major contribution to the growth rate of these waves The source of the wave bursts is spread out in space and not confined near the neutral plane